Characterization and optimization of bioflocculant derived through implementation of submerged and solid-state fermentation of Bacillus subtilis UPMB13 - Zulkeflee, Zufarzaana (2014)
Breakthroughs in bioproduction field have opened up vast opportunities in the exploration of bio-based products as substitutes to chemical derivatives for water treatment technologies. In that framework the interest of finding an ecologically benign solution specifically focusing on treating suspended solids pollution was explored. As production cost becomes the limiting factor which restricts wider applications of bioproducts for alternative water treatment, fermentation technology was applied in this study; basic substrates were utilized through non-elaborative techniques for bioproduction of a biopolymeric flocculant. The main goal of this study is to produce a biopolymer with flocculating capabilities which can substitute the commonly used commercial flocculants through two fermentation strategies; namely, the submerged (SmF) and solid-state (SSF) fermentations. The flocculating performances were measured through kaolin assays based on the clarity of the suspension and the visible flocs formed after treatment with the bioflocculant. The characterizations of the bioflocculants produced were scrutinized for further understanding of their nature and properties which contributed to their flocculating abilities. The bioflocculant produced through the better fermentation strategy was further studied for its flocculating performances and in comparison to other commercial flocculants. A novel low molecular weight (10-50 x 103 Da), high flocculating biopolymer denoted as UPMBF13 was successfully produced through de novo pathway from the SmF and the SSF of Bacillus subtilis UPMB13. It was found to consist of poly-γ-glutamic acid and polysaccharide derivatives, with hydroxyl, carboxyl, methoxyl and carbonyl functional groups and was either fibrous (SmF) or granular (SSF) in natures, which are the major known characteristics of a bioflocculant. The best production strategy for UPMBF13 was found to be through the SmF by manipulating the optimum conditions (media: no additional supplement; duration: 24-72 hrs; temperature: 25-30oC; pH: 7.0-8.0; shaking speed: 100-200 rpm) for growth. This led to a maximum performance of 95% in flocculating activity with large visible floc formations, comparable to those from the commercial flocculant polyacrylamide (maximum activity: 98%), and superior to that of polyaluminium chloride (maximum activity: 47%). The production of UPMBF13 through SSF was also verified to be possible, but yielded an inferior product (maximum activity: 71%) with barely any flocs formed upon treatment. Furthermore, the SmF strategy yielded at an average two-fold the amount of UPMBF13 at 2.70 g/L while the SSF produced about 1.25 g/kg in 72 hrs. Overcoming the inferior performance of the SSF by scaling-up the process to a pilot-scale level (near-to-adiabatic, non-sterilized condition with continuous oxygen flow) led to a competitive environment where the autochthonous microbes proliferated over UPMB13 and produced their own bioflocculants which obscured the performance of UPMBF13. In general, the results from this study confirmed that the production of UPMBF13 is feasible through de novo pathway with no additional input of L-glutamic acid supplement. High flocculating performance was achieved solely with basic substrates without further manipulations and modifications. Furthermore, UPMBF13 is cation-independent once extracted and purified, requiring no additional cation source for its application in suspended solid treatments.